The Effect of Cucumber (Cucumis Sativus) Feeding on the Estrus Cycle in Female Mice (Mus musculus) - Fassa Atif Aprilia; Harlita Harlita (Biology, Medicine, & Natural Product Chemistry, 2026)
Cucumbers (Cucumis sativus) are plants that contain bioactive compounds such as flavonoids and phytoestrogens that resemble the hormone estrogen, so they have the potential to affect the reproductive system. One of the indicators of the balance of reproductive hormones in female animals is the etrus cycle. An imbalance of the hormones estrogen and progesterone can cause changes in the duration of the etruscan cycle. This study aims to determine the effect of cucumber extract administration on the estrus cycle of female rats (Mus musculus). This study is an experimental study with Complete Random Design (CRD). A total of 9 female rats were divided into three groups, namely the control group, the treatment group with a dose of 200 mg/kg body weight, and the treatment group with a dose of 300 mg/kg body weight. Cucumber extract is administered orally for 15 days. Observation of the estrus cycle is carried out daily by the vaginal swab method. The data were analyzed using a one-way analysis of variance test. The results showed that the average duration of the estrus cycle of the control group was 4.8 days, the 200 mg/kg BB dose treatment group was 6.1 days, and the 300 mg/kg BB dose treatment group was 4.6 days. The results of statistical analysis showed that the administration of cucumber extract did not have a significant effect on the estrus cycle of female mice (p > 0.05). It can be concluded that administration of cucumber extract at doses of 200 mg/kg BB and 300 mg/kg BB did not have a significant effect on the estrus cycle of female rats, although there is a tendency to alter the length of the estrus phase in some individuals.